2017
DOI: 10.1073/pnas.1617066114
|View full text |Cite
|
Sign up to set email alerts
|

SNAT7 is the primary lysosomal glutamine exporter required for extracellular protein-dependent growth of cancer cells

Abstract: Lysosomes degrade cellular components sequestered by autophagy or extracellular material internalized by endocytosis and phagocytosis. The macromolecule building blocks released by lysosomal hydrolysis are then exported to the cytosol by lysosomal transporters, which remain undercharacterized. In this study, we designed an in situ assay of lysosomal amino acid export based on the transcription factor EB (TFEB), a master regulator of lysosomal biogenesis that detects lysosomal storage. This assay was used to sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 47 publications
(85 reference statements)
4
60
0
Order By: Relevance
“…Interestingly, while it has been appreciated that a lysosomal protein must exist for leucine efflux (Milkereit et al, 2015; Taylor, 2014), no such transporter had been identified. Recent work identified SLC38A7 as an effluxer of glutamine from lysosomes (Verdon et al, 2017). …”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, while it has been appreciated that a lysosomal protein must exist for leucine efflux (Milkereit et al, 2015; Taylor, 2014), no such transporter had been identified. Recent work identified SLC38A7 as an effluxer of glutamine from lysosomes (Verdon et al, 2017). …”
Section: Resultsmentioning
confidence: 99%
“…In Homo sapiens, at least 17 known AAAP 31 members were found 9 , spanning across solute carrier families SLC32, SLC36 and SLC38, 32 although none of these structures have been determined to date. Thus far, 11 members of SLC38 33 have been identified in humans 10 , two of which, SLC38A7 and SLC38A9, localize at lysosomes 34 5,11,12 . SLC38A9 is the only member of this family known to participate in the Ragulator-Rag 35GTPases complex and in turn plays an important role in the amino acid dependent activation of 36 mTORC1 3,5,[13][14][15] .…”
mentioning
confidence: 99%
“…This theory can also be applied to SLC38A7 and SLC38A8 which also are phylogenetically closely related and co-expressed on most neurons (Hägglund et al, 2015 ) and initially regulated in the opposite direction after partial amino acid starvation, and in the hypothalamic cell line Slc38a7 was transcriptionally induced while Slc38a8 was not. In a previous study, SLC38A7 co-localized with lysosomes in HeLa cells and was found to mediate flux of glutamine and asparagine and hence crucial for growth of cancer cells (Verdon et al, 2017 ). SLC38A9 is located on lysosomes and is a component of the amino acid sensing Ragulator-Rag complex responsible for activation of mTORC1 (Jung et al, 2015 ; Rebsamen et al, 2015 ; Wang et al, 2015 ) and in mouse brain SLC38A9 immunostaining is detected in both GABAergic and glutamatergic neurons (Hellsten et al, 2017a ).…”
Section: Discussionmentioning
confidence: 94%